Indoor thermoregulatory homeostasis using hydrodynamic instability - Raphael Kay; Ross J. Cocks; Charles Katrycz; J. Alstan Jakubiec; Atalaya Milan Wilborn; Rafiq Omair; Joanna Aizenberg; Benjamin D. Hatton (Proceedings of the National Academy of Sciences, 2026)
Branching patterns can emerge when one fluid is injected into a more viscous one within a quasi-two-dimensional cavity. While these patterns have dazzled physicists for decades, modern engineering efforts have focused on suppressing, rather than leveraging, these flow instabilities. Here, by designing fluidic devices with calibrated geometries, liquid absorptivities, and rheology, we exploit the thermal sensitivity of the Saffman–Taylor instability to achieve thermoregulatory shading systems with self-adjustment capabilities. Our devices produce negative feedback branching patterns that reduce indoor solar heating when warm but increase it when cool. Moreover, compared to existing temperature-responsive shading approaches with fixed thermal behaviors, our system can switch its thermal sensitivity and indoor temperature setpoints on-demand by adjusting the rate that patterns are grown. Experiments and models reveal the energy savings and indoor climate control capabilities enabled by this thermoregulatory framework. Overall, our work provides a blueprint for designing materials with self-regulatory behaviors based on flow instabilities.